2016
DOI: 10.1038/gim.2015.111
|View full text |Cite
|
Sign up to set email alerts
|

Utility of whole-genome sequencing for detection of newborn screening disorders in a population cohort of 1,696 neonates

Abstract: Purpose:To assess the potential of whole-genome sequencing (WGS) to replicate and augment results from conventional blood-based newborn screening (NBS). Methods:Research-generated WGS data from an ancestrally diverse cohort of 1,696 infants and both parents of each infant were analyzed for variants in 163 genes involved in disorders included or under discussion for inclusion in US NBS programs. WGS results were compared with results from state NBS and related follow-up testing.Results: NBS genes are generally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
123
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 112 publications
(130 citation statements)
references
References 31 publications
(34 reference statements)
0
123
0
7
Order By: Relevance
“…The SFWG hopes this process of nominations and updates will serve as a reference point in related efforts, such as initiatives that apply genetic and genomic testing in public health programs and population screening. Successful efforts have already been directed toward evaluating the efficacy of newborn screening panels in detecting genetic diseases, 21,22 and a similar approach could begin to evaluate the utility of certain applications of genomic screening in healthy adults. The reporting of SFs presents significant opportunities to prevent disease, but this process may introduce fiscal and other costs, including those associated with further confirmatory testing.…”
Section: Assessing the Impact Of Secondary Findingsmentioning
confidence: 99%
“…The SFWG hopes this process of nominations and updates will serve as a reference point in related efforts, such as initiatives that apply genetic and genomic testing in public health programs and population screening. Successful efforts have already been directed toward evaluating the efficacy of newborn screening panels in detecting genetic diseases, 21,22 and a similar approach could begin to evaluate the utility of certain applications of genomic screening in healthy adults. The reporting of SFs presents significant opportunities to prevent disease, but this process may introduce fiscal and other costs, including those associated with further confirmatory testing.…”
Section: Assessing the Impact Of Secondary Findingsmentioning
confidence: 99%
“…Pushing this envelope, a recent study has compared the results of standard newborn screening, which is typically performed within 48 h of birth, to exome sequencing, although this is not yet feasible on a population scale. 1 Additional studies are underway to further this comparison and to analyze the ethical, legal, and social implications of such testing in a newborn population. [2][3][4] Clinical exome sequencing, removed from the newborn screening setting, relies on a combination of accurate clinical information submitted by the ordering provider and careful variant interpretation from the reporting laboratory.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the results of the study by Bodian et al, 18 reported herein, will be of broad interest to readers of Genetics in Medicine. In the first prospective study of its kind, they compared the relative diagnostic yield of traditional NBS with NBS-by-WGS for 65 genes in 1,696 predominantly healthy newborns.…”
Section: Commentarymentioning
confidence: 57%